2013
DOI: 10.1371/journal.pone.0056716
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Muscle Cell Metabolism and Mechanotransduction Are Associated with Myopathic Phenotype in a Mouse Model of Collagen VI Deficiency

Abstract: This study identifies metabolic and protein phenotypic alterations in gastrocnemius, tibialis anterior and diaphragm muscles of Col6a1−/− mice, a model of human collagen VI myopathies. All three muscles of Col6a1−/− mice show some common changes in proteins involved in metabolism, resulting in decreased glycolysis and in changes of the TCA cycle fluxes. These changes lead to a different fate of α-ketoglutarate, with production of anabolic substrates in gastrocnemius and tibialis anterior, and with lipotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 80 publications
5
25
0
Order By: Relevance
“…We found that the expression profiles of Col6a1 −/− and WT gastrocnemius were clustered together and therefore similar. Indeed this supports the existing knowledge about muscle involvement in the Col6a1 −/− mouse model, where gastrocnemius is very mildly affected, whereas tibialis and even more diaphragm are severely affected (De Palma et al, 2013). In contrast, diaphragm and tibialis anterior Col6a1 −/− muscles clustered together and were clearly separate from their WT counterparts, suggesting that ColVI deficiency severely and similarly affects these muscle types (Fig.…”
Section: Overall Gene Expression Profile In Col6a1supporting
confidence: 87%
See 3 more Smart Citations
“…We found that the expression profiles of Col6a1 −/− and WT gastrocnemius were clustered together and therefore similar. Indeed this supports the existing knowledge about muscle involvement in the Col6a1 −/− mouse model, where gastrocnemius is very mildly affected, whereas tibialis and even more diaphragm are severely affected (De Palma et al, 2013). In contrast, diaphragm and tibialis anterior Col6a1 −/− muscles clustered together and were clearly separate from their WT counterparts, suggesting that ColVI deficiency severely and similarly affects these muscle types (Fig.…”
Section: Overall Gene Expression Profile In Col6a1supporting
confidence: 87%
“…We show major transcriptional changes in the diaphragm and tibialis anterior, accordingly to the proteomic findings (De Palma et al, 2013). All muscles shared similar alterations in genes involved in the inflammatory response, cell proliferation, −/− and wild-type (Ctrl) mice revealed a significant upregulation (*P<0.05, t-test) of CLOCK protein levels in the diaphragm and tibialis anterior, whereas the MAT2a protein level was significantly altered in tibialis anterior and gastrocnemius, which showed an increase and decrease, respectively.…”
Section: Col6a1supporting
confidence: 69%
See 2 more Smart Citations
“…Summarizing, after subacute exposure to hypobaric hypoxia, the muscle starts controlling HIF‐1α hydroxylation and behaves as a producer of substrates controlling de novo protein synthesis, sarcoplasmic reticulum Ca 2+ release, ROS generation as well as the activation of detrimental pathways known to drive the metabolic machinery toward accumulation of lipogenic citrate . Thus, in this phase, energy‐sparing mechanisms contribute mainly to the maintenance of energetic and redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%